Frontier in functional manufacturing technologies : selected, peer reviewed papers from the 2nd International Conference on Functional Manufacturing Technologies (ICFMT 2010), Aug. 6-9 2010, Harbin, Heilongjiang, China - Zuo, Dunwen (Advanced materials research ;, 2010)
The major topics covered by the special volumes include anti-fatigue design and anti-fatigue manufacturing, manufacturing systems and reliability, processing detection and monitoring-control, CIMS and management systems, production system and simulation technology, quality control of manufacturing systems, agile manufacturing, finite-element analysis and structure optimization, digital manufacturing and robotics, rapid prototyping technology, reverse engineering technology, high-speed (ultra high-speed) precise cutting technology, ultra-precise processing technology, micro machining technology, pattern recognition technology, image processing technology, sensor and signal detection technology, non traditional machining technology, mine equipment manufacturing and technology, advanced manufacturing system and technologies and so on.